Replication Data for: Risk perception and decision-making: do farmers consider risks from climate change? - Eitzinger, Anton; Binder, Claudia R.; Meyer, Markus A. (International Center for Tropical Agriculture, 2019)
Data were collected during interviews with experts and farmers in Cauca between July and October 2014. After finishing both interview series, we analyzed the differences in perception between experts and farmers. To aggregate the individual rankings, we calculated a weighted average based on the ranking of each element for the four questions. We compared the average experts’ rankings to farmers’ rankings stratified by gender and age group and then applied the hierarchical clustering approach to the farmers’ rankings to obtain groups of farmers with similar choices.